(untitled) (Annual of the Faculty of Philosophy in Skopje, 2008)
In grave 295 from the complex Vodocha Churches in the village of Vodocha near Strumica, burial artifacts have been discovered that represent a rarity not only for this necropolis, but also for the Republic of Macedonia. The deceased had been buried with a morning star, having an iron head with characteristic six spikes, which was placed next to his right shoulder, as well as with a silver ring on his right index finger that bore a seal marking his lineage (Fig. 2-4). During the Medieval and post-Medieval period, the morning star was a popular weapon. At the same time, because it resembled a sceptre, it symbolized the high social status of its bearer. This has also been confirmed in the epic poetry cycle about the mythical hero Krali Marko. By its shape and seal, the ring from grave 295 has been brought into connection with the markings of the knightly order of the dracon, formed by the Hungarian king in 1408. The order was noted in the Balkan countries (also in Macedonia) during the 15th century and in later references among the archaeological materials found in the following century (Maneva 2007, cat. no. 46; Maneva, 2007/j, 383-395). The decadent styling of the ring from grave 295 (Fig. 4) may suggest a later date of manufacture (after the middle of the 15th century), while the great damage to it signifies long-term use by several generations of heirs, so that the ring may have made it to the grave by the end of the 15th or the 16th century at the earliest. The bearer of the morning star and the ring from grave 295 was a young male. He was buried with these artifacts-insignia as a descendant of renowned Christian gentry, most probably from the class of lesser nobility (the medieval proniar). These families, even during the Turkish Ottoman period, had at their disposal inheritable estates called „ bashti- ni “ (heritages), andfrom their lines „ voynuk-i “ (soldiers) were recruited who were duty-bound to join the Turkish army when called; every year this was done by another family member. In addition to this status, the ring on the right index finger shows that this man was also a member of the knightly order of the dracon. The existence of, bashtinari “ (heirs to the estates) in Vodocha has been confirmed several times in the records of the Turkish census, where even their names have been listed. The archaeological findings from the Vodocha necropolis - the rings, above all, but also the other jewelry - reveal the crests and the emblems of renowned families, as well as the insignia of the knightly order of the dracon (Fig. 4-5).